Red runaways: hypervelocity stars, hills ejecta, and other outliers in the f-to-m star regime - Vickers, John J.; Smith, Martin C.; Grebel, Eva K. (The astronomical journal, 2015)
In this paper we analyze a sample of metal-rich (>−0.8 dex) main sequence stars in the extended solar neighborhood, investigating kinematic outliers from the background population. The data, which are taken from the Sloan Digital Sky Survey, are kinematically profiled as a function of distance from the Galactic plane using full six-dimensional phase space information. Each star is examined in the context of these kinematic profiles and likelihoods are assigned to quantify whether a star matches the underlying profile. Since some of these stars are likely to have been ejected from the disk, we trace back their orbits in order to determine potential ejection radii. We find that objects with low probability (i.e., “outliers”) are typically more metal-poor, faster and, most importantly, have a tendency to originate from the inner Galaxy compared to the underlying population. We also compose a sample of stars with velocities exceeding the local escape velocity. Although we do not discount that our sample could be contaminated by objects with spurious proper motions, a number of stars appear to have been ejected from the disk with exceptionally high velocities. Some of these are consistent with being ejected from the spiral arms and hence are a rich resource for further study. Finally we look at objects whose orbits are consistent with them being ejected at high speeds from the Galactic center. Of these objects we find that one, J135855.65+552538.19, is inconsistent with halo, bulge and disk kinematics and could plausibly have been ejected from the Galactic nucleus via a Hills mechanism.